Exclusive contracts and bargaining power - Hiroshi Kitamura; Noriaki Matsushima; Misato Sato (Osaka University, Institute of Social and Economic Research (ISER), 2016)
This study constructs a simplest model to examine anticompetitive exclusive contracts that prevent a downstream buyer from buying input from a new up-stream supplier. Incorporating Nash bargaining into the standard one-buyer-one-supplier framework in the Chicago School critique, we show a possibility that an inefficient incumbent supplier can deter a socially efficient entry through exclusive contracts.
Keywords: L12; L41; L42; C72; 330; Antitrust policy; Entry deterrence; Exclusive contracts; Nash bargaining